Exploring women's work decision in Malaysia / Peck-Leong Tan … [et al.] - Tan, Peck-Leong; Baah, Ruzita; Subramaniam, Geetha; Iberahim, Hadijah (Penerbit UiTM (UiTM Press), 2015)
Over the years, the educational level of Malaysian women has increased tremendously with more women than men in the tertiary institutions. Nevertheless, investment in female human capital has not been translated into more women in the workforce. Therefore this study aims to explore the work decision of Malaysian women. Results from the survey of 553 women reveal that nearly all women expressed that they are willing to work after completing their tertiary education but they feel that support and influence from families are the most important decidingfactors in influencing womens decision to work. Furthermore, economic and social differences also play vital roles in women's work decision. Women from poorer families and with lower educational background tend to focus on their financial needs as priority in their work decision. On the other hand, women with higher educational background and who come from richer families tend to choose jobs that will allow them to achieve their goals and also bring great self satisfaction. Therefore, various strategies targeting different women need to be done to increase the labour force participation of Malaysian women.